ANALISIS PENGARUH FEEDING PADA PROSES GRINDING JOURNAL TERHADAP NILAI KUALITAS CAMSHAFT TYPE 2TNV70 PASCA IQT - Sudja Rizki Maulana (KALPIKA, 2022)
Research in the field of machining in testing the level of roughness needs to be done to get good results in themachining process. The purpose of this study was to determine the effect of variations in feeding on thesurface grinding process on the surface roughness and hardness of S45C carbon steel that has gone throughprocesses including induction, quenching and tempering and to compare which feeding variation has thelowest level of roughness. The research method used is an experimental method in the form of giving avariety of feeding which is tested on 4 samples in the surface grinding process. The number of variationsgiven is 0.2mm/min, 0.4mm/min, 0.8mm/min, 1.2mm/min. The test results obtained are in the form ofroughness values and hardness values on specimens that have been previously tested. The results showedthat there was a change in the roughness value that occurred during the grinding process by applying a0.2mm/min feeding variation resulting in an average value of 1.33683333µ, a feeding variation of0.4mm/min producing an average value of 1.27068333µ, a feeding variation of 0.8mm/min producing anaverage value of 1.27068333µ. the average value is 1.29633333µ, the variation of feeding 1.2mm/minproduces an average value of 1.39458333µ and there is no significant change in the surface hardness valuein the surface grinding process. The tools used in this study were the Mitutoyo SV2100 rougness tester todetermine the roughness value, and the Sonohard SH22 hardness tester to determine the hardness value. Thedata that has been obtained are then analyzed using descriptive statistics where the data are presented in theform of tables and graphs. after grinding. This shows that there is an effect of giving different variations offeeding the surface grinding process to the surface roughness value.